The Simulation of Incompressible Fluid in Lid-Driven Cavity using COMSOL - Syahirah Mohammad Rafee,; Muhamad Ghazali Kamardan, (Enhanced Knowledge in Sciences and Technology, 2023)
The simulation of incompressible fluid in lid-driven cavity has been carried out. In this study, COMSOL Multiphysics 6.0 was used as a tool to implement the solution with approximate result. The aim of this study is to apply COMSOL in solving the problem regarding fluid flow in lid-driven cavity and compare the streamline provided with the previous study by Munir et al. The dimensionless governing equations of the flow were modelled in COMSOL to plot the streamlines and velocity magnitudes for different values of Reynolds number. This study shows that the position of primary vortex is significantly affected by the Reynolds number. Also, the velocity of primary vortex increases as the Reynolds number increase.